Update on the SedLine algorithm for calculating the Patient State index of older individuals during general anesthesia: a randomized controlled trial - Obara, Shinju; Oishi, Rieko; Nakano, Yuko; Noji, Yoshie; Ebana, Hideaki; Isosu, Tsuyoshi; Kurosawa, Shin; Murakawa, Masahiro (Minerva anestesiologica, 2021)
The SedLine sensor processes raw electroencephalogram (EEG) signals and displays the depth of sedation as a Patient State index (PSi). Reliance on standard processed EEG data and failure to recognize age-related effects can lead to an erroneous interpretation that low-amplitude EEG findings in an older patient signify an insufficient depth of anesthesia presented as abnormally high PSi values (AHPSi). We hypothesized that the incidence of AHPSi would decrease with the use of the recently-updated version of the SedLine sensor, in which the bispectral index (BIS) values were used to titrate anesthesia. Thirty-three patients undergoing sevoflurane-remifentanil anesthesia were randomized into two groups. SedLine sensors designed based on an old (v.1203) or updated (v.2000) algorithm were used. The BIS (v.4.1) and absolute index of total EEG power (TP) were simultaneously recorded. The attending anesthesiologists titrated the anesthetics, and BIS was maintained at 40-60. The incidence of AHPSi (PSi>50 with BIS 40-60) was calculated during the first 30 min after the start of surgery. Compared to the old algorithm group, the incidence of AHPSi was significantly lower in the updated algorithm group (26.7% vs. 4.2%, P<0.001). Lower TP values and the use of the old algorithm have significant effect on increased PSi values (p<0.001). The incidence of AHPSi decreased with the use of the updated version of the SedLine algorithm.